CHARACTERIZATION AND ELECTROCHEMISTRY OF LiFePO4 BY SONICATIONHYDROTHERMAL METHODS - Wagiyo Honggowiranto; Evvy Kartini (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2016)
CHARACTERIZATION AND ELECTROCHEMISTRY OF LiFePO4 BY SONICATIONHYDROTHERMAL METHODS. Cathode materials of LiFePO4 for rechargeable-lithium ion battery were synthesized by combination of sonication and hydrothermal method. The reaction has been carried out by mixing of FeSO4.7H2O, H3PO4, LiOH and ethylene glycol. The mixtures were sonicated by ultrasonic prior to a hydrothermal process. The crystal structure, microstructure and electrical properties of LiFePO4 products were characterized by usingX-ray diffraction (XRD), a Scanning ElectronMicroscope (SEM), and an Impedance Spectroscopy, respectively. The X-ray data showed that the crystal structure of LiFePO4 belongs to the P m n a space group (olivine structure). The crystalline size of sample non-sonic, sonic and commercial LiFePO4 were 730.2; 3068.0 and 639.4 Å, respectively. Performances of half cell batteries were measured by Impedance spectroscopy and by using Battery Analyzer BST-8.The EIS data from half cell batteries of nonsonic, sonic and commercial LiFePO4 were 269.92; 149.85 and 106.2 Ω, respectively. Meanwhile, the specific capacities at 0.1C of non-sonic, sonic and commercial LiFePO4 were 98.70; 120.17 and 125.23 mAh/g, respectively.As confirmed by SEM image, the particle distribution of sonic-LiFePO4 were more homogenous, and had properties similar to the commercial ones. It is concluded that the sonication procedure carried out prior to hydrothermal has improved performance of the lithium ion battery.